Atypical Odontalgia: Case Review and Literature on Variations in Clinical Features and Therapeutic Response - Susanna Halim; Ivanka Ivanka (Pascasarjana, Mataram University, 2026)
Atypical Odontalgia (AO) is a complex chronic pain condition, characterized by tooth or tooth socket pain without a clear clinical or radiographic cause. This condition, also known as phantom tooth pain or persistent dentoalveolar pain disorder, poses a diagnostic challenge for dental practitioners, often leading patients to undergo multiple ineffective dental procedures. To review variations in clinical features of AO and diverse therapeutic responses based on data from various journals. AO is highly variable in presentation, including pain described as heavy, splitting, stabbing, burning, or electric shock-like. The pain may be unilateral or bilateral, difficult to localize, and often significantly affects patients’ quality of life. Psychiatric comorbidities in AO patients, including depression and anxiety disorders, can worsen the condition. Reports also suggest associations between AO and neurodevelopmental disorders such as ADHD and ASD, highlighting the importance of a holistic approach in diagnosis and management. Therapeutically, AO shows heterogeneous responses to various interventions. Antidepressants such as amitriptyline have been reported effective, though patient responses vary. Other cases show successful outcomes with atypical antipsychotics such as aripiprazole, either as monotherapy or in combination with mirtazapine. Another approach under investigation is the use of OnabotulinumtoxinA (OnabotA), which has shown promising results in reducing pain intensity in AO patients without significant side effects. Psychological therapies and behavioral support are also considered crucial, especially when psychiatric comorbidities are present, to improve treatment outcomes and patients’ quality of life. A deeper understanding of AO’s clinical variability and therapeutic responses is essential for more accurate diagnosis and effective management